Studi Literatur: Pengaruh Model Pembelajaran Berbasis Proyek dalam Meningkatkan Hasil Belajar Siswa: Array - Nur Afifah Nabila Saragih; Neviyarni (eductum: Jurnal Literasi Pendidikan, 2022)
The right learning models will be very influential in student learning outcomes. So students can good learning outcomes. This study aims to analyze the effect of project based learning models in improving student learning outcomes. The method used is literature analysis, ini this case analyzing previous research journals. This project based learning can be one of the innovation learning models carried out by teachers to students are more activa and learning becomes more meningful becase it develops a real product. The results of the study found that this project based learning model had an effect on improving student learning outcomes.